CORRELATION OF GDP AND NATIONAL WEALTH AS KEY INDICATORS OF COUNTRY'S ECONOMIC DEVELOPMENT - Fufalko , I. Yu. (The actual problems of regional economy development, 2020)
The article investigates the economic importance of the key indicators of the national accounts system as a gross domestic product (GDP) and national wealth and their role in assessing the country`s economic situation. National wealth is defined as the aggregate of natural, industrial (industrial) and human capital in one forty countries of the world. Interdependence and interdependence between these indicators of economic development are analyzed. The main factors influencing the efficiency and productivity of the use of national wealth are determined. To measure the effectiveness of using the country’s national wealth, an economic indicator such as ROE is calculated by dividing GDP into national wealth adjusted for the value of net foreign assets. Among the 140 countries in the world, the average level of use of national wealth in the TOP-10 most developed countries is 6.98%, in the top-40 - 7.08%. The average level of national wealth productivity in countries with a 40 to 90 rating position is 7.92%, while in the 50 poorest and least developed countries, it stands at 5.37%.